Oxygen-defect-rich coating with nanoporous texture as both anode host and artificial SEI for dendrite-mitigated lithium–metal batteries. Issue 9 (4th February 2021) - Wu, Qingping; Yao, Zhenguo; Du, Aochen; Wu, Han; Huang, Minsong; Xu, Jun; Cao, Fahai; Li, Chilin
Abstract : An unusual oxygen-defect-rich nanoporous MgO x coating bonded with carboxyl-rich carbon wires (MgO x –C) is proposed simultaneously as 3D monolithic host and artificial SEI film to achieve dendrite-free Li metal batteries. Abstract : The fragility of the natural solid electrolyte interphase (SEI) and deformability of the naked Li anode cannot meet the requirements of high coulombic efficiency (CE) and long-period cycling for Li metal batteries (LMBs). Accordingly, conductive porous anode hosts with surface decoration/defect modulation appear to be an effective solution to restrain the growth of Li dendrites. Herein, we propose an unusual oxygen-defect-rich nanoporous MgO x coating bonded with carboxyl-rich carbon wires (MgO x –C), which act as a 3D monolithic host and artificial SEI film simultaneously, to achieve dendrite-free LMBs. The enrichment of the lithiophilic (carboxyl groups) and anionphilic (oxygen defects) sites could homogenize the Li deposition process, accommodate the anode volume variation, and mitigate the depletion of the space charge. The highly defective MgO x enabled fast charge transfer, thus result in a high-rate Li plating performance. The initial nucleation and following plating behaviors of Li were significantly optimized by the conversion and alloying reactions between the Li and MgO x domains. The resultant Li@MgO x –C electrode enabled a stable Li plating/stripping process with a low overpotential and high CE, even under the high plating capacity of 10 mA h cm −2 and high current density of 15 mA cm −2 .